ETIOLOGY, PRESENTATION AND MANAGEMENT OUTCOME OF PNEUMOTHORAX - Khan, Nisar; Wazir, Mohammad Salim; Yasin, Mohammad; Mohammad, Jan; Javed, Arshad (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried to determine etiology, presentation, complications and management outcomes of pneumothorax in patients presenting at two hospitals in NWFP province of Pakistan.. Methods: Pneumothorax patients reporting at the chest unit of Post Graduate Medical Institute, Lady Reading Hospital, Peshawar, and Pulmonology unit of Ayub Teaching Hospital, Abbottabad from 1999 to 2002 were included in the study. Patients of all ages were included. They were admitted and followed up to the full recovery/late complications. Results: A total of 146 pneumothorax patients reported during this period. Majority of the patients were diagnosed to have pneumothorax due to pulmonary tuberculosis making about 36.30% of the total cases. Second most common cause was primary spontaneous pneumothorax (19.86%). Bacterial infections were also sizeable at 16.43%. Other causes included COPD, Asthma, Iatrogenic, Interstitial lung disease, tuberous sclerosis and bronchiectasis. Conclusion: It was concluded from this study that pulmonary tuberculosis is the commonest cause of pneumothorax in our setup. KEY WORDS: Pneumothorax, Tuberculosis, Pulmonary, Lung diseases, Obstructive